All Days 1999
DOI: 10.2118/52729-ms
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Characterization of Residual NAPL Distribution Using Streamline-Based Inversion of Partitioning Tracer Tests

Abstract: Identifying the location and distribution of NAPL (Non Aqueous Phase Liquid) in the subsurface constitutes a vital step in the design and implementation of aquifer remediation schemes. In recent years, partitioning interwell tracer tests (PITT) have gained increasing popularity as a means to characterize NAPL distribution in-situ. In this method, a conservative and a partitioning tracer are injected into the contaminated site. The chromatographic separation between the conservative and the partitioning tracer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Yoon et al 12 demonstrated the utility of the streamline-based inversion method for estimating non-aqueous phase liquid (NAPL) saturation in an aquifer from PITT data and applied the method to a set of tracer tests carried out in a test cell at the Hill Airforce Base. In this paper we show how a field-scale PITT data can be analyzed using the streamline-based inverse method.…”
Section: Spe 71320mentioning
confidence: 99%
“…Yoon et al 12 demonstrated the utility of the streamline-based inversion method for estimating non-aqueous phase liquid (NAPL) saturation in an aquifer from PITT data and applied the method to a set of tracer tests carried out in a test cell at the Hill Airforce Base. In this paper we show how a field-scale PITT data can be analyzed using the streamline-based inverse method.…”
Section: Spe 71320mentioning
confidence: 99%
“…More importantly, we can compute sensitivities of the production response to reservoir parameters analytically using a single forward simulation. 4,5,9,10 • Hierarchical Parameterization. Unknown reservoir properties are parameterized in a hierarchical fashion according to the data resolution.…”
Section: Approachmentioning
confidence: 99%
“…We have addressed these issues in detail in our previous publications. 4,10 Utilizing these features, we can effectively decouple the forward modeling and inversion to further increase the computational speed. Our approach involves decomposing the inverse problem by scale and integration of production data by a scale-by-scale inversion.…”
Section: Multiscale Inversion: Mathematical Formulationmentioning
confidence: 99%
“…Oil distribution between wells is derived by matching the tracer production profiles using a 3D finite difference simulator such as UTCHEM 6,7 or by a streamline model. 8,9 To circumvent the technical problems encountered in simulation, an analytical chromatographic transformation method was proposed by Tang 2-4 and Wood et al 5 and a moment-analysis method [10][11][12][13] to calculate S orw directly by comparing the relative separation of tracers. Chromatographic transformation was employed by and Wood et al 5 to determine S orw for the Golden Spike, Judy Creek, and Leduc interwell partitioning tracer tests.…”
Section: Introductionmentioning
confidence: 99%